The Role of Nutrition Education in Management of Diabetes Mellitus - Nwafor, Afoke (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2017)
Nutrition therapy occupies a very important position in health care delivery. This is because most noncommunicable diseases such as hypertension, diabetes and malnutrition among others can be prevented and controlled through proper nutrition. This paper thus focuses on the role of nutrition education in the management of diabetes mellitus. The use of nutrition in diabetes management aims at preventing the disease, managing existing condition as well as reducing the rate of developing complications. The general guidelines for individuals with all types of diabetes is to achieve and maintain a reasonable body weight by adoption of healthy food choices from carbohydrates, proteins, vitamins, fats and oil, mineral salts and roughages . The introductory aspect of the paper gave an overview of the concept of diabetes mellitus capturing its prevalence in Nigeria, definition, types, signs and symptoms and complications. The paper also discusses the role of nutrition education in diabetes management by articulating its usefulness in enhancing diabetic patient’s knowledge, attitude and compliance to nutritional recommendations. Numerous nutritional teachings which should form part of nutrition education programme were identified and discussed. These include teachings on carbohydrate counting and portion sizes, reduction of saturated fatty acid and cholesterol consumption, balanced meal, dietary integration of insulin therapy, alcohol use in diabetes and nutritional guide for specific population. Important teaching Tips in diabetes nutrition education are also presented. The paper concludes that diabetes nutrition education is a vital tool in diabetes management and thus should be geared towards meeting individual nutritional needs of diabetics. Finally, the paper recommends among others that health care providers should focus on nutrition counseling rather than micronutrient supplementation in diabetic patients and diabetes nutrition education should be individualized.